Prevalence of postpartum depression and its association with diabetes mellitus among mothers in public health facilities in Mbarara, Southwestern Uganda - Atuhaire, Catherine; Taseera, Kabanda; Atukunda, Esther C; Atwine, Daniel; Matthews, Lynn T; Rukundo, Godfrey Zari (Psychology, Health & Medicine, 2024)
Postpartum Depression (PPD) is a major health challenge with potentially devastating maternal and physical health outcomes. Development of diabetes mellitus has been hypothesized as one of the potential adverse effects of PPD among mothers in the postpartum period, but this association has not been adequately studied especially in low resource settings. This study aimed at determining prevalence of postpartum depression and its association with diabetes mellitus among mothers in Mbarara District, southwestern Uganda. We conducted a facility based cross-sectional study of 309 mothers between 6th week to 6th month after childbirth. Using proportionate stratified consecutive sampling, mothers were enrolled from postnatal clinics of two health facilities, Mbarara Regional Referral Hospital and Bwizibwera Health center IV. PPD was diagnosed using the Mini-International Neuropsychiatric Interview (MINI 7.0.2) for the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5). Diabetes mellitus was diagnosed by measuring Hemoglobin A1c (HbA1c). Logistic regression was used to determine the association of PPD and diabetes mellitus among mothers. The study established that PPD prevalence of PPD among mothers of 6th weeks to 6th months postpartum period in Mbarara was 40.5% (95% CI: 35.1–45.1%) and it was statistically significantly associated with diabetes mellitus in mothers between 6 weeks and 6 months postpartum. The prevalence of diabetes mellitus among mothers with PPD was 28% compared to 13.6% among mothers without PPD. Mothers with PPD had 3 times higher odds of being newly diagnosed with diabetes as compared to those without PPD (aOR = 3.0, 95% CI: 1.62–5.74, p = 0.001). Mothers with PPD between 6 weeks and 6 months postpartum are more likely to have diabetes mellitus as compared to those without PPD. Well-designed prospective analytical studies are needed to conclude on the risk of diabetes mellitus in relation to PPD. Early screening of PPD may be considered in postpartum mothers.
Keywords: Postpartum; Diabetes mellitus; Depression; Prevalence; Maternal mental health